If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 46 + -46x = (7x + 3)(x + -1) Reorder the terms: 46 + -46x = (3 + 7x)(x + -1) Reorder the terms: 46 + -46x = (3 + 7x)(-1 + x) Multiply (3 + 7x) * (-1 + x) 46 + -46x = (3(-1 + x) + 7x * (-1 + x)) 46 + -46x = ((-1 * 3 + x * 3) + 7x * (-1 + x)) 46 + -46x = ((-3 + 3x) + 7x * (-1 + x)) 46 + -46x = (-3 + 3x + (-1 * 7x + x * 7x)) 46 + -46x = (-3 + 3x + (-7x + 7x2)) Combine like terms: 3x + -7x = -4x 46 + -46x = (-3 + -4x + 7x2) Solving 46 + -46x = -3 + -4x + 7x2 Solving for variable 'x'. Reorder the terms: 46 + 3 + -46x + 4x + -7x2 = -3 + -4x + 7x2 + 3 + 4x + -7x2 Combine like terms: 46 + 3 = 49 49 + -46x + 4x + -7x2 = -3 + -4x + 7x2 + 3 + 4x + -7x2 Combine like terms: -46x + 4x = -42x 49 + -42x + -7x2 = -3 + -4x + 7x2 + 3 + 4x + -7x2 Reorder the terms: 49 + -42x + -7x2 = -3 + 3 + -4x + 4x + 7x2 + -7x2 Combine like terms: -3 + 3 = 0 49 + -42x + -7x2 = 0 + -4x + 4x + 7x2 + -7x2 49 + -42x + -7x2 = -4x + 4x + 7x2 + -7x2 Combine like terms: -4x + 4x = 0 49 + -42x + -7x2 = 0 + 7x2 + -7x2 49 + -42x + -7x2 = 7x2 + -7x2 Combine like terms: 7x2 + -7x2 = 0 49 + -42x + -7x2 = 0 Factor out the Greatest Common Factor (GCF), '7'. 7(7 + -6x + -1x2) = 0 Factor a trinomial. 7((1 + -1x)(7 + x)) = 0 Ignore the factor 7.Subproblem 1
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Subproblem 2
Set the factor '(7 + x)' equal to zero and attempt to solve: Simplifying 7 + x = 0 Solving 7 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + x = 0 + -7 x = 0 + -7 Combine like terms: 0 + -7 = -7 x = -7 Simplifying x = -7Solution
x = {1, -7}
| p=12x-5x | | 6-4x=4(1-x) | | 35-(2x-14)=40-(x+2) | | (2x^2)-x-(3)=0 | | 5x^2=23x+10 | | 40-7n=2(-5n+6)-n | | 8w/6+8=w-2 | | 12(4x-6)=8x+5(8x-6) | | 6s=-3T | | 5s=8t+12 | | 4(2x-1)-(-3x-5)=-179 | | 10b+5=76+5 | | 49-84x+36x^2=0 | | 3z+8=12+3z-z | | 2=.10p | | v^2+16v-g^2+64=0 | | 4+x=-3+y | | 5x-2=5x-12 | | 5(x+8)-2x=60 | | 3x+10-6=7 | | 10=-3F+10N | | (x+3)-27=30 | | 26+13x=12(x+2) | | -2+2=0+2 | | 2x-6=-x+2 | | 6x+11=8x+15 | | 5=4F-5N | | 3(a-1)+2(6+2a)=8a-6-5+a | | 5k-9/4=k | | -9-5k=-24 | | 3x+2+y=22 | | c-22=-27 |